2023
DOI: 10.3389/fcvm.2023.1227818
|View full text |Cite
|
Sign up to set email alerts
|

Integrative single-cell analysis of cardiac and pulmonary sarcoidosis using publicly available cardiac and bronchoalveolar lavage fluid sequencing datasets

Abstract: IntroductionCardiac presentation of autoimmune sarcoidosis, known as cardiac sarcoidosis (CS), is a poorly understood disease with high mortality and low diagnosis rate. While CS is an immunological syndrome, little is known about how cardiac parenchymal and stromal cells mediate its pathogenesis. Moreover, while most current sarcoidosis research is based on research in pulmonary sarcoidosis (PS), it remains unclear how much both presentations of sarcoidosis overlap. To tackle these concerns, we leveraged publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Although the specific antigen is unidentified, studies indicate the involvement of T cells, particularly IFN-γ-producing Th17 cells, as a key immunologic feature in sarcoidosis. 216,217 Recent research utilizing single-cell or single-nuclei RNA sequencing revealed that distinct macrophage subsets from different origins contribute to sarcoidotic granuloma formation in the heart, with upregulated mTOR (mammalian target of rapamycin) signaling and alternative activation pathway as well as downregulated cytokine signaling and phagocytosis functions. 194,217 These studies further demonstrated a dysregulated transcription program in nonhematopoietic resident heart cells under conditions of cardiac sarcoidosis including profibrotic, proinflammatory fibroblasts; fibroblast-like, angiogenic endothelial cells; and proinflammatory, stressrelated cardiomyocytes.…”
Section: Cardiac Sarcoidosismentioning
confidence: 99%
See 1 more Smart Citation
“…Although the specific antigen is unidentified, studies indicate the involvement of T cells, particularly IFN-γ-producing Th17 cells, as a key immunologic feature in sarcoidosis. 216,217 Recent research utilizing single-cell or single-nuclei RNA sequencing revealed that distinct macrophage subsets from different origins contribute to sarcoidotic granuloma formation in the heart, with upregulated mTOR (mammalian target of rapamycin) signaling and alternative activation pathway as well as downregulated cytokine signaling and phagocytosis functions. 194,217 These studies further demonstrated a dysregulated transcription program in nonhematopoietic resident heart cells under conditions of cardiac sarcoidosis including profibrotic, proinflammatory fibroblasts; fibroblast-like, angiogenic endothelial cells; and proinflammatory, stressrelated cardiomyocytes.…”
Section: Cardiac Sarcoidosismentioning
confidence: 99%
“…216,217 Recent research utilizing single-cell or single-nuclei RNA sequencing revealed that distinct macrophage subsets from different origins contribute to sarcoidotic granuloma formation in the heart, with upregulated mTOR (mammalian target of rapamycin) signaling and alternative activation pathway as well as downregulated cytokine signaling and phagocytosis functions. 194,217 These studies further demonstrated a dysregulated transcription program in nonhematopoietic resident heart cells under conditions of cardiac sarcoidosis including profibrotic, proinflammatory fibroblasts; fibroblast-like, angiogenic endothelial cells; and proinflammatory, stressrelated cardiomyocytes. These findings are further supported by an animal study showing that the activation of mTOR signaling specifically in CD11c-expressing cells in mice resulted in a granulomatous phenotype and fibrosis in the heart, resembling cardiac sarcoidosis in humans, suggesting mTOR signaling as a potential therapeutic target (Table ).…”
Section: Cardiac Sarcoidosismentioning
confidence: 99%